Resistance training instuction upper body - Aarberg, Everet; Fink, Doug; Human Kinetics (Firm) (Illnois : Human Kinetic, 2001)
This program demonstrates exercices that focus on the larger pushing and pulling movements. Pushing and pressing exercices that target the chest, anterior deltoid, and associated triceps are presented at several angles with numerous variations
Title from title screen
Scripwriter, R. Chris Johns, Everett Aaberg
Keywords: Weight training; Exercise; Personal trainers